Analisis Komparatif Pendapatan Layanan Penjualan Offline dan Online: Studi Kasus Soulja Coffee - Nurhaliza, Jelita; Hermawan, Adam; Zahra, Nasywa; Fazri, Rezi Muhammad; Yanti, Septi Dwi; Maulid, Zaki Nuraziz; Maesaroh, Syti Sarah (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study aims to analyze the difference in revenue performance between offline and online sales channels at Soulja Coffee during December 2024. The population in this research includes all sales transactions that occurred at Soulja Coffee within the specified period. The sample consists of daily revenue data from each sales channel, selected using purposive sampling based on relevance and data availability. Data were collected through documentation from Soulja Coffee’s internal financial reports. The research employs a comparative quantitative approach and utilizes the Independent T-Test for statistical analysis, supported by SPSS software to test the proposed hypothesis. The results indicate a significant difference in revenue between online and offline sales channels, with the average revenue from online sales (mean = 13.4844) being higher than that of offline sales (mean = 13.1091). These findings have important implications for decision-making in the planning and evaluation of sales strategies. Moreover, the results can serve as a valuable consideration in developing a business model that is more adaptive to changes in consumer behavior and the dynamics of the digital market.